Current state of the art in hypoplastic left heart syndrome - Birla, Aditya K.; Brimmer, Sunita; Short, Walker D.; Olutoye, Oluyinka O.; Shar, Jason A.; Lalwani, Suriya; Sucosky, Philippe; Parthiban, Anitha; Keswani, Sundeep G.; Caldarone, Christopher A.; Birla, Ravi K. (Frontiers in Cardiovascular Medicine, 2022)
Hypoplastic left heart syndrome (HLHS) is a complex congenital heart disease in which a neonate is born with an underdeveloped left ventricle and associated structures. Without palliative interventions, HLHS is fatal. Treatment typically includes medical management at the time of birth to maintain patency of the ductus arteriosus, followed by three palliative procedures: most commonly the Norwood procedure, bidirectional cavopulmonary shunt, and Fontan procedures. High survival rates are now obtained at tertiary treatment centers, though adverse neurodevelopmental outcomes remain a clinical challenge. The genetic basis of this condition has not fully been elucidated, though mutations in several candidates have been postulated to be responsible. Stem cell therapy has been evaluated to increase right ventricle ejection fraction, though it is in a stage of infancy and of only marginal functional benefit to the patient. Recent innovations in tissue engineering and regenerative medicine promise to provide important tools to both understand the underlying basis of HLHS as well as provide new therapeutic strategies. In this review article, we provide a broad overview of HLHS, starting with a historical description and progressing through a discussion of the genetics, surgical management, post-surgical outcomes, stem cell therapy, hemodynamics and tissue engineering approaches.